Controlled Resistant Hypertension Following A Successful Renal Artery Stenting: A Rare Case Report in A Developing Country - Munita, Fatihatul Firdaus; Tiksnadi, Badai Bhatara; Martha, Januar Wibawa; Ratna, Margareta Ginanti (Jurnal Kardiologi Indonesia, 2024)
Background Renal artery stenosis is among the etiologies of secondary hypertension in which the diagnosis and therapy are difficult. We report a case of a patient with uncontrollable hypertension with frequent episodes of malignant hypertension, treated with renal artery stenting. Case Illustration A 36-year-old female visited the cardiovascular polyclinic on a common control for her hypertension. She was diagnosed with hypertension two years, and she had several episodes of malignant hypertension. At the beginning of her treatment, she has prescribed an angiotensin-converting-enzyme inhibitor, yet her pressure was uncontrolled and worsened. By the visit, she was treated using two alpha-2-adrenergic agonists, a loop diuretic, a beta-blocker, a calcium-channel blocker, an angiotensin-receptor blocker, and an aldosterone-receptor antagonist without any satisfactory outcome on her blood pressure status. She had a blood pressure of 196/130 mmHg with tachycardia of 112 times/minute. We found cardiomegaly on physical examination, which was proven by a chest x-ray. Echocardiography indicated hypertensive heart disease. Screening for secondary hypertension, including laboratory tests (complete blood count, potassium, sodium, creatinine, fasting glucose, lipid profile, urinalysis, thyroid-stimulating hormone, and 24-hour urinary-free cortisol), suggested normal results. Renal ultrasound and doppler were also conducted and showed a suspicion of right renal artery stenosis. Therefore, angiography of the renal artery was performed for diagnosis and therapy when indicated. The angiography suggested a normal left renal artery, while the right artery had a 95% stenosis on the proximal part. An intravascular ultrasound-guided percutaneous transluminal angioplasty on her right renal artery was conducted, and two vascular stents were implanted. The patient showed a remarkable development following her decreasing blood pressure on follow-up. After one week, her blood pressure is controllable on a single antihypertensive and antiplatelet therapy. Conclusion The diagnosis and management of a patient with resistant hypertension might be challenging, particularly in the setting of a developing country. Renal artery angiography, among other examinations, might be crucial in the diagnosis sequence, yet it was only sometimes readily available. We present a case in which a diagnosis of renal artery stenosis was made, followed by a definite treatment resulting in unprecedented hypertension control. An identifiable etiology is the key to a proper and the best treatment option for the patient.